Highland Rural Welfare - Purwandaya, Budhi; Agustin, Heny (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol 18 No 1 (2024): Vol 18 No 1 (2024)DO - 10.24843/SOCA.2024.v18.i01.p02, 2024)
Welfare, as the purpose of all economies, is often held backed poverty in economic society. Numerous studies indicated a negative correlation between access to clean water and poverty levels, particularly in rural areas in the highlands where people experience difficulties in procuring clean water. The study of poverty is indirectly related to the level of welfare. Nevertheless, the focus on welfare is still relatively lesser than on poverty. This study is aimed to conduct an empirical study of rural welfare in the highlands by analyzing the determinants that influence the occurrence of different classifications on people's welfare levels. The study was conducted in Bantaragung Village, Sindangwangi District, Majalengka Regency, West Java with a sample of 750 households. This study employed a welfare dimension approach by using socio-demographic and economic variables, including access to clean water, as well as a multidimensional poverty approach which was then modeled in an ordered logit. The results found indicated that the socio-demographic variables that determine the level of family welfare were the age of head of the family and the number of family members along with their education. Meanwhile, the economic variables that influence it were asset ownership and income levels.